Avaliação da resposta inflamatória sistêmica após o implante de stents coronários em pacientes em uso de rapamicina por via oral - Rosa, Werther Clay Monico [UNIFESP] (2010)
Recent findings in basic and experimental science have supported the notion that atherosclerosis is characterized by a chronic inflammatory vascular response and it is not only a bland lipid storage disease. It is also well known that coronary artery stenting is associated with both local vascular and systemic inflammation, which in turn correlate with increased in-stent restenosis after percutaneous coronary interventions. Sirolimus is an immunossupressant drug approved in the United States to prevent renal transplant rejection. Sirolimus has proved effective to prevent and treat in-stent restenosis (ISR) both with systemic administration and local administration through drug-eluting stents. We studied the effect of oral sirolimus administered to prevent and treat instent restenosis (ISR), on the variation of serum levels of inflammatory markers following coronary stenting. All patients had clinicaly manisfested ischemia. One group of patients at high risk for ISR received a loading dose of 15 mg sirolimus and 5 mg daily thereafter 28 days after stenting (SIR-G). Whole blood concentrations of sirolimus were obtained weekly and drug dose was adjusted accordingly. A control group (CONT-G) was submitted to stenting without sirolimus therapy. Both groups were followed for 8 weeks. Peripheral blood samples were obtained before the procedure (baseline), and 24h, 1 week, 4 weeks and 8 weeks after the procedure. The following biomarkers were evaluated: high sensitivity C-reactive protein (hs-CRP), soluble interleukin-2 receptor alpha (IL-2sRα), monocyte chemoattractant protein-1 (MCP-1), matrix metalloproteinase 2 (MMP-2), matrix metalloproteinase 9 (MMP-9), tissue inhibitor of MMP-1 (TIMP-1), intercellular adhesion molecule-1 (ICAM-1) P-selectin, interleukin-6 (IL-6) and Macrophage colony-stimulating factor (M-CSF). Samples were centrifugated and serum was stored at -85°C. At baseline, SIR-G had higher levels of MMP-9 and TIMP-1 and CONT-G had higher levels of ICAM-1. At follow-up, the increase in high sensitivity C-reactive protein concentration was highest at 24 h after stenting in both SIR-G and CONT-G. After adjustment for baseline values, a marginally significant difference between the groups was observed at 1 week (-0.90±4.3 vs 0.03±0.3, P = 0.0726), which became significant at 4 weeks (-1.50±5.0 vs -0.19±0.4, P = 0.008) and lost significance 1 month after sirolimus discontinuation (-1.73±4.3 vs -0.01±0.7, P = 0.0975). A continuous fall in MMP-9 concentration was observed in SIR-G, with the greatest reduction at 4 weeks, while a positive variation was noted at week 8, 4 weeks after sirolimus discontinuation. SIR-G and CONT-G variations were different at 1 week (-258.9 ± 510 vs +363 ± 438, P = 0.0030) and 4 weeks (-352.9 ± 455 vs +395.2 ± 377, P = 0.0004). ICAM-1 levels were lower in SIR-G throughout the study. After baseline adjustment, significant differences appeared at week 1 (-13.1 ± 49.7 vs -16.4 ± 119.1, P = 0.0047) and week 4 (-3.3 ± 46.0 vs 3.8 ± 138.4, P = 0.0096). SIR-G exhibited a higher increase in P-selectin after sirolimus discontinuation at week 8 after baseline adjustment (46.1±67.9 vs 5.8±23.7, P = 0.0025). The other biomarkers presented only minor changes. The These findings suggest that the anti-restenotic actions of systemic sirolimus include anti-proliferative effects and modulation of the inflammatory response with inhibition of adhesion molecule expression.